2012
DOI: 10.1186/1687-9856-2012-18
|View full text |Cite
|
Sign up to set email alerts
|

Home blood sodium monitoring, sliding-scale fluid prescription and subcutaneous DDAVP for infantile diabetes insipidus with impaired thirst mechanism

Abstract: Background/AimsInfants with diabetes insipidus (DI), especially those with impaired thirst mechanism or hypothalamic hyperphagia, are prone to severe sodium fluctuations, often requiring hospitalization. We aimed to avoid dangerous fluctuations in serum sodium and improve parental independence.MethodsA 16-month old girl with central DI, absent thirst mechanism and hyperphagia following surgery for hypothalamic astrocytoma had erratic absorption of oral DDAVP during chemotherapy cycles. She required prolonged h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Patients are furthermore prescribed desmopressin (DDAVP) to achieve a urine output of 1.5-2 liters daily. The dosage of desmopressin varies, as well as formulation (oral: 100- 250 micrograms twice daily; intranasal 3-10 micrograms twice per day) [ 62 , 63 ]. Oral absorption is often less preferable due to the significant variation with individuals and must be taken on an empty stomach [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients are furthermore prescribed desmopressin (DDAVP) to achieve a urine output of 1.5-2 liters daily. The dosage of desmopressin varies, as well as formulation (oral: 100- 250 micrograms twice daily; intranasal 3-10 micrograms twice per day) [ 62 , 63 ]. Oral absorption is often less preferable due to the significant variation with individuals and must be taken on an empty stomach [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some pediatric endocrinologists have prescribed a home sodium monitoring device for patients with adipsic DI in combination with a sliding-scale fluid prescription plan, with an 84% success rate in maintaining plasma sodium at the reference range [ 17 ]. Unfortunately, this device is not always available.…”
Section: Discussionmentioning
confidence: 99%
“…His DI was successfully managed with a purely weight-based protocol guiding fluid intake. Hameed et al [8] reported on a pediatric patient (age 16 months) whose sodium levels varied dramatically, with both hypernatremia and hyponatremia. This fluctuation was thought to be partially related to an infantile drive to drink that is motivated not only by thirst but by hunger.…”
Section: Discussionmentioning
confidence: 99%